2022
DOI: 10.3390/su142315832
|View full text |Cite
|
Sign up to set email alerts
|

Tourism and Natural Hazards: River Landform Changes Due to Geohazards and Its Influence on the Economic Development of Ecotourism in Sabah, Malaysia

Abstract: Geohazards are often portrayed as a calamity that has a detrimental effect on humans and the environment. It is usually uncommon to consider geohazards in the opposite context. Therefore, this study examines the positive effects of an earthquake event centered in Ranau, Sabah, especially from the aspect of ecotourism development. A total of 27 homestay entrepreneurs in Kampung Melangkap were interviewed in this study. The raw data collected during the interview were conceptually and descriptively analyzed usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Several studies have been conducted to assess the water quality of rivers in various cities [19]. The population growth, industrialisation, and rapid economic development in urban areas have led to major changes of natural landscapes, land use, land cover, and ecosystems [20][21][22]. Previous research demonstrated how landscape changes caused by human activities have a significant impact on rivers, particularly the alterations to water chemistry and sediment concentration [23].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been conducted to assess the water quality of rivers in various cities [19]. The population growth, industrialisation, and rapid economic development in urban areas have led to major changes of natural landscapes, land use, land cover, and ecosystems [20][21][22]. Previous research demonstrated how landscape changes caused by human activities have a significant impact on rivers, particularly the alterations to water chemistry and sediment concentration [23].…”
Section: Introductionmentioning
confidence: 99%
“…In determining the specific geomorphosite of an area, data synthesis is carried out (Reynard and Panizza, 2005;Panizza and Piacente, 2008;González Amuchastegui et al, 2013;Santos et al, 2019;Jafar et al, 2022;Ilie and Grecu, 2023;Sánchez-Almodóvar et al, 2023). As an example of a case in the study area, the specific geomorphosite is fault geoforms (Evelpidou et al, 2021;Puswanto et al, 2022;Dóniz-Páez and Becerra-Ramírez, 2023).…”
Section: Introductionmentioning
confidence: 99%